ReL-SSHI rectifier based piezoelectric energy harvesting circuit with MPPT control technique. (March 2022) - Shen, Jiahui; Xia, Yinshui; Xia, Huakang
Abstract: Rectifier-Less Synchronized Switch Harvesting on Inductor (ReL-SSHI) interface is one of the most efficient interfaces for weakly-coupled piezoelectric (PE) systems. However, ReL-SSHI interface has narrow optimal rectified voltage range. Therefore, in this paper a maximum power point tracking (MPPT) circuit is presented for ReL-SSHI interface. An envelope extractor and a hysteresis voltage controller are used in the MPPT, which can monitor the open circuit (OC) voltage of piezoelectric transducer (PZT) during Energy Harvesting (EH). Simulation shows the maximum MPPT efficiency can reach up to 99.1% and the Figure of Merit (FoM) factor can achieve 6.4. The measurements confirm the simplicity and efficiency of the proposed MPPT solution for the weakly-coupled piezoelectric energy harvesting (PEH).